The Role of Jasa Raharja Company in Providing Accident Guarantees for Traffic Victims of North Sumatra Province - Indah Mutiara Rizky; Muhammad Arief (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
PT Jasa Raharja (Persero) is a social insurance company that prioritizes services to the community, especially those who are victims of traffic accidents and general passengers. PT Jasa Raharja as a State-Owned Enterprise (BUMN) that provides basic compensation and protection to the community, especially to victims of accidents on public passenger transportation and road traffic. Based on Law Number 33 of 1964 concerning the Mandatory Passenger Accident Insurance Fund and Law Number 34 of 1964 concerning Road Traffic Accident Funds, apart from providing basic protection to victims of passenger and road traffic accidents, Jasa Raharja's main task is also to collect and manage funds. community to meet people about compensation rights. This study aims to determine the extent to which the role of PT Jasa Raharja (Persero) in providing insurance compensation for victims of traffic accidents and public transport passengers at the North Sumatra branch office has operated effectively and efficiently in accordance with Laws Number 33 and 34 of 1964.